Hubungan Kepatuhan Minum Obat dengan Terkontrolnya Kadar Gula Darah pada Pasien Diabetes Melitus Tipe II di RSU Islam Harapan Anda Kota Tegal - Mae Septiana; Herry Susanto; Kurnia Wijayanti (Asosiasi Riset Ilmu Kesehatan Indonesia, 2025)
Diabetes Mellitus is a complication caused by severe disturbances, particularly in the metabolic composition of carbohydrates, fats, and proteins in the body. The level of patient compliance in taking medication is one of the factors that determine the success of diabetes mellitus therapy. Compliance with treatment plays a crucial role in controlling metabolic conditions, especially in diabetes mellitus patients. The impact of non-compliance with medication in type II diabetes mellitus patients will increase uncontrolled blood sugar levels, which can lead to various complications of organ damage. The purpose of this study was to examine the relationship between medication compliance and blood sugar levels in type 2 diabetes mellitus patients at Harapan Anda Islamic Hospital in Tegal City. This study used a quantitative cross-sectional approach. The sample size was 58 respondents using a purposive sampling technique. Data analysis techniques used univariate and bivariate analysis (chi-square). Characteristics of 58 patients suffering from type 2 diabetes mellitus at Harapan Anda Islamic General Hospital, Tegal City, most of them are aged 46-60 years, with female gender, with most of them having junior high school education, some with working status, with a duration of suffering for >5 years, most with moderate medication adherence and most with normal blood sugar levels. There is a relationship between medication adherence and blood sugar levels in type 2 diabetes mellitus patients at Harapan Anda Islamic General Hospital, Tegal City (0.000). It is hoped that it can provide valuable information for diabetes sufferers about the importance of medication adherence to blood sugar levels so that blood sugar levels can be controlled.